The Electronic Structural and Defect-Induced Absorption Properties of a Ca2B10O14F6 Crystal - Xuejiao Wang; Benyan Xu; Kunpeng Wang; Zhenyou Li; Jianxiu Zhang; Lanju Liang; Longfei Li; Yanbiao Ren; Yong Liu; Meng Liu; Dongfeng Xue (Crystals, 2021)
Comprehensive ab initio electronic structure calculations were performed for a newly developed deep-ultraviolet (DUV) non-linear optical (NLO) crystal Ca2B10O14F6 (CBOF) using the first principle method. Fifteen point defects including interstitial, vacancy, antisite, Frenkel, and Schottky of Ca, O, F, and B atoms in CBOF were thoroughly investigated as well as their effects on the optical absorption properties. Their formation energies and the equilibrium concentrations were also calculated by ab initio total energy calculations. The growth morphology was quantitatively analyzed using the Hartman–Perdok approach. The formation energy of interstitial F (Fi) and antisite defect OF were calculated to be approximately 0.33 eV and 0.83 eV, suggesting that they might be the dominant defects in the CBOF material. The absorption centers might be induced by the O and F vacancies (VF, VO), interstitial B and O (Oi, Bi), and the antisite defect O substitute of F (OF), which might be responsible for lowering the damage threshold of CBOF. The ionic conductivity might be increased by the Ca vacancy (Vca), and, therefore, the laser-induced damage threshold decreases.